Evolution of catalyst coated atomised magnesium spheres – An alternative thermal storage medium for concentrated solar power applications. (23rd November 2017) - Mistry, Priyen C.; Grant, David M.; Stuart, Alastair D.; Manickam, Kandavel; Walker, Gavin S.
Abstract: Elevated temperature cycling studies were performed on two commercial gas atomised Mg spherical powders (average diameter of 26 μ m and 30 μ m) with magnetron sputtered catalysts (chromium, iron, vanadium and stainless steel) applied to their surfaces. At 350 °C, the presence of a catalyst promotes faster reaction kinetics with improving capacity until approaching stabilisation by the 90th cycle, e.g. the normalised capacity of V_Mg30 was found to rise from 45.5% to 65.5%. Following determination of activation energies (from Kissinger plots) and microstructural analysis of the post cycled structures a mechanism was proposed for the differing evolutions of the uncoated and coated Mg powders based upon a complex process in which particle sintering competes with particle fragmentation. Catalyst effectiveness varied with temperature, having a negligible impact on hydrogen storage characteristics of the atomised Mg powders following 50 cycles at 400 °C and this was mainly associated with the lack of multivalency in the catalysts. Highlights: Catalyst coatings improve the hydrogenation properties of atomised Mg if cycled at 350 °C. Cr_Mg26 reached 73% (5.50 wt%) in 30 min in the 90th cycle at 350 ° C. At 350 ° C, particle fragmentation dominates particle sintering for catalysed samples. Catalyst coatings have a negligible impact on atomised Mg during cycling at 400 ° C.